INCREASING THE BIOLOGICAL VALUE OF YEAST TEST DUE TO THE USE OF SKIMMED RAW MATERIALS - POPOVA, SVITLANA; HOPKALO, LARISA; HVOZDIK, ANASTASIIA; SHVEN, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The prospects of using dry protein-carbohydrate semi-finished product (SBVN) in yeast dough technology are proved. The indicators of active and titrated acidity of the dough were studied, the presence in the system of SBVN helps to reduce the active and increase the titrated acidity of dough samples. The positive effect of SBVN on the quality of gluten dough has been proved. It is established that the use of SBVN in the technological process of yeast dough production provides an opportunity to adjust the strength of the flour and purposefully influence the rheological properties of the dough. As a result of the conducted researches it is established: • For indicators of active acidity it is established that the use of SBVN with a concentration of 5; 10 and 15% helps to reduce the active acidity, which reaches its optimal pH value of 5.71… 5.72 after 90 · 60 s of fermentation. Sample dough with a concentration of SBS 20% reach the same pH value after (180… 210) · 60 s fermentation, due to reduced activity of lactic acid bacteria and inhibition of yeast activity • The titer of titratable acidity in samples with a concentration of SBVN 5; 10 and 15% increases rapidly and reaches the optimal value of 3.2… 3.30H after 90 · 60 s of fermentation. The sample of the test with a concentration of SBVN 20% reaches the optimal value of the titrated acidity after (150… 180) · 60 s of fermentation, which is explained by the decrease in the activity of lactic acid bacteria. • Adding SBVN to the dough leads to an increase in the yield of dry gluten by 2-7% for the batch of flour №1 and by 2-9% for the batch №2. The elasticity indicators increase by 15% for the flour lot №1 and decrease by 5% for the flour lot №2. There is also an increase in the elongation of gluten by 16% for a batch of flour №1 and a decrease in this indicator for a batch of flour №2 by 5%. SBVN helps to increase the amount of crude gluten by 2-13% for the batch of flour №1 and 5-7% for the batch №2 compared to the control. • At this stage of research, the optimal concentration of SBVN to the weight of flour was 15%.